Peran Pembelajaran Bahasa dan Sastra Indonesia dalam Membentuk Karakter Pada Era Vuca - Syamsuri, Andi Sukri; Bur, Eka Yulianti (ppjbsip, 2023)
This study aims to describe the Role of Learning the Indonesian Language and Literature in Character Building during the VUCA Era. In carrying out this research, the authors used a descriptive-qualitative approach. The source of the data in this study was the Class X High School/Vocational High School Indonesian Language Teaching Material Books published by the Ministry of Education, Culture, Research and Technology, the Agency for Research and Development and Books, and the Center for Curriculum and Books. The number of pages in this book consists of 248 pages. The data in this study are in the form of clauses, sentences, and images containing 18 characters set by the Ministry of National Education. The results showed that: 1) The character of creativity is described through a text entitled